Consumer Empowerment Profile in Rural and Urban Area - Simanjuntak, Megawati; Amanah, Siti; Puspitawati, Herien; Asngari, Pang S (UI Scholars Hub, 2021)
The purpose of this research was to analyze the profile of consumer empowerment and the influence of demographic characteristics, socio-economic status and cosmopoliteness on consumer empowerment in rural and urban area. The research finding indicated a low consumer empowerment in urban and rural area. In general, most respondents who were not categorized as empowered consumer were aged >37 years old, working in rural areas, included in income category ranged IDR 397,874.57/capita/month both in rural and urban areas, family size of ≤ 4 persons in rural areas,length of education ≤9 years in rural areas and not cosmopolite in rural areas. Higher level of education and the more cosmopolite the respondents would increase consumer empowerment both in ruraland urban area. One of the attempts in empowering consumers is by intensifying consumer education involving government, NGOs, and private sector.